2017
DOI: 10.1080/00981389.2017.1316811
|View full text |Cite
|
Sign up to set email alerts
|

Examining the inter-correlated effects of low income, life stress, and race on birth outcomes: A representative state study

Abstract: Programming of the stress response system during gestation has lifelong effects that put the infant at risk for multiple stress-related pathologies. Populations most vulnerable to prenatal stress are African-Americans and individuals of low socioeconomic status. The Pregnancy Risk Assessment Monitoring System (PRAMS) research project, a collaboration between the Centers for Disease Control and Prevention and individual state health departments, was employed for this study. Tennessee data from 2009 were compile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 41 publications
1
24
0
Order By: Relevance
“…In addition, the dataset did not provide socioeconomic information such as marital status, employment status, or education level. We may assume that women enrolled in Medicaid are likely to share certain sets of socioeconomic characteristics, such as low-income status [12,13,18,19]. However, future research should include ways to categorize pregnant women enrolled in Medicaid, considering risky behaviors, daily lifestyle, and social support elements.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, the dataset did not provide socioeconomic information such as marital status, employment status, or education level. We may assume that women enrolled in Medicaid are likely to share certain sets of socioeconomic characteristics, such as low-income status [12,13,18,19]. However, future research should include ways to categorize pregnant women enrolled in Medicaid, considering risky behaviors, daily lifestyle, and social support elements.…”
Section: Discussionmentioning
confidence: 99%
“…As race/ethnicity is interwoven with multiple social, economic, and cultural issues, however, the precise cause of this disparity is not clearly known. Social determinants of health, such as maternal educational level, family income, housing situation, partner support as well as community factors can also play an important role in accounting for these disparities in preterm birth outcomes [1,[12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies were conducted to investigate the effect of SES on prematurity. Some of these studies showed an association, while others did not [ 5 - 7 ]. These contrasting results may be explained by the differences in predictors and measurements used in each study.…”
Section: Introductionmentioning
confidence: 99%
“…Although pregnancy can be a joyous moment in a woman's life, it may also induce a great amount of stress, leading to a number of negative health consequences for mothers and their infants. For instance, recent systematic reviews and meta‐analyses have shown pregnancy‐specific stressors (e.g., concerns about baby's health) and other stressors during this time period (e.g., finances and lack of support) to be significant predictors of maternal depressive symptoms (Yim, Tanner Stapleton, Guardino, Hahn‐Holbrook, & Dunkel‐Schetter, ), premature births, low birthweight, and long‐term problems in infant emotional and behavioural development (Bussières et al, ; Graignic‐Philippe, Dayan, Chokron, Jacquet, & Tordjman, ), with low‐income women being at greater risk for these adverse health outcomes (Lefmann, Combs‐Orme, & Orme, ; Reynolds, Labad, Buss, Ghaemmaghami, & Räikkönen, ). To better understand how prenatal stress impacts health, studies that examine women's responses to stressors during pregnancy are needed.…”
Section: Introductionmentioning
confidence: 99%